A meta-analysis of genome-wide association studies to identify candidate genes for feed efficiency traits in pigs - Silva, Maria Rita Gonçalves da (2024)
The pig production industry is an activity of great importance for the economic and social scenarios of the Brazilian and world markets. The growing prominence of feed efficiency traits in production systems, due to their impact on production costs and the environment, has increased the importance given to these traits in animal breeding programs. Genome wide association studies (GWAS) have emerged as an important methodology for assessing the genetic background of complex traits, contributing to a better biological understanding of the trait under study. In this context, this study was carried out with the main objective of identifying and validating candidate genes associated with feed conversion ratio (FCR) and residual feed intake (RFI) through a systematic review and meta-analysis of GWAS in pigs. The systematic review was conducted to compile the studies that would make up the database. For the meta-analysis, information on the significant markers, including associated p-values and number of observations, was extracted from each article. The METAL software was used to implement the meta- analysis. After the meta-analysis, Bonferroni correction was applied considering an alpha of 0.05 to establish statistically significant associations for the genome-wide significance level, by dividing alpha by the number of SNPs tested in the meta-analysis. The significant SNPs in the meta-analysis were used to identify candidate genes. An enrichment analysis was conducted using the Database for Annotation, Visualization, and Integrated Discovery (DAVID). The results of the systematic review revealed 13 studies, of which 10 evaluated FCR and 6 evaluated RFI, identifying a total of 160 markers for FCR and 96 for RFI. After the meta-analysis, 145 and 90 markers were significantly associated with FCR and RFI, respectively. The gene annotation process resulted in 105 and 114 genes for FCR and RFI, respectively. The enrichment analysis for FCR resulted in 16 significant gene ontology (GO) terms, while 6 terms were identified for RFI. The MED18, PHACTR4, ABCC2, TRHDE, FRS2, FAR2 and FIS1 genes stand out as strong candidates for FCR, and the ADGRL2, ASGR1, ASGR2 and MAN2B1 genes for RFI. Keywords: Feed conversion ratio; Residual feed intake, GWAS.